The Big Society in a Time of Crisis—The Impact on Public Health. (October 2013) - Halsall, Jamie P.; Wankhade, Paresh; Cook, Ian G.
At the time of writing, the UK is in a "double-dip" recession with the economy flatlining. The Government is set for a new round of benefit cuts. The cuts introduced to the public sector when the coalition government came to power in May 2010 are already beginning to bite. This "age of austerity" and general gloom was lifted briefly in summer 2012 by the undoubted success of the London Olympics and Paralympics; however, the sense of crisis within the nation runs deep. This article explores the extent to which the concept of the "Big Society" can alleviate the impact of the crisis on public health. The authors explore the thinking behind the concept of "Big Society" tracing related ideas back to Victorian times. We further examine this issue, citing evidence about the impact of cuts on the National Health Service's ambulance service and how social capital offers a way forward. While acknowledging that there is merit in the Big Society's call for voluntary sector support, beyond the support provided by the State, the authors argue that the reality of the Big Society is nonetheless flawed. If anything, the call should be for a "Little Society" of voluntarism at a local level, where meaningful voluntary action can help ameliorate the inevitable forecast decline in state support.